2008
DOI: 10.1139/x07-126
|View full text |Cite
|
Sign up to set email alerts
|

Transaction evidence analysis: stumpage prices and risk in central Georgia

Abstract: This paper uses hedonic regression techniques to analyze timber bid transactions in central Georgia. Softwood stumpage prices from pay-as-cut transactions are regressed against timber sale and stand characteristics. We identify observable factors that are statistically associated with the volatility of pine sawtimber stumpage prices in the market. The remaining price volatility, defined as market risk, characterizes undiversifiable price volatility in the market. Isolating market risk in this way has implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Although the pine stumpage price showed mainly a decreasing tendency, there were some main fluctuations in stumpage price change during the research period. It is likely that such a situation have also contributed to relatively low R-squared values, compared to other similar research using hedonic price function (Buongiorno and Young 1984;Puttock et al 1990;Leefers and Potter-Witter 2006;Sydor and Mendell 2008). Variables describing year, contract length, number of bids, harvest type, grade, market conditions, and logging conditions are statistically significant based on corresponding probabilities.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Although the pine stumpage price showed mainly a decreasing tendency, there were some main fluctuations in stumpage price change during the research period. It is likely that such a situation have also contributed to relatively low R-squared values, compared to other similar research using hedonic price function (Buongiorno and Young 1984;Puttock et al 1990;Leefers and Potter-Witter 2006;Sydor and Mendell 2008). Variables describing year, contract length, number of bids, harvest type, grade, market conditions, and logging conditions are statistically significant based on corresponding probabilities.…”
Section: Resultsmentioning
confidence: 78%
“…Based on empirical results, they found that the models within the same geographic region cannot be transferred easily to other regions. Sydor and Mendell (2008) analyzed timber bid transactions using hedonic regression techniques in central Georgia. They estimated a regression model of softwood stumpage prices from pay-as-cut transactions against timber sale and stand characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Stands with seasonal harvest restrictions have to be harvested during suitable weather conditions, while stands with no seasonal harvest restrictions can be harvested according to demand. MacKay and Baughman (1996), Sydor and Mendell (2008) and Brown et al (2012) also found that harvest restrictions lowered the willingness to pay for standing timber.…”
Section: Harvest Restrictionsmentioning
confidence: 92%
“…Load volumes in transport have also been found to be on average lower for pulpwood than for sawlogs (Nurminen and Heinonen 2007). Sydor and Mendell (2008) also found that a higher percentage of pulpwood within a particular sale lowered stumpage prices.…”
Section: Timber Assortmentmentioning
confidence: 92%
See 1 more Smart Citation